The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/nbm.3614
|View full text |Cite
|
Sign up to set email alerts
|

Determination of an optimally sensitive and specific chemical exchange saturation transfer MRI quantification metric in relevant biological phantoms

Abstract: The purpose of this study was to develop realistic phantom models of the intracellular environment of metastatic breast tumour and naïve brain, and using these models determine an analysis metric for quantification of CEST MRI data that is sensitive to only labile proton exchange rate and concentration. The ability of the optimal metric to quantify pH differences in the phantoms was also evaluated.Novel phantom models were produced, by adding perchloric acid extracts of either metastatic mouse breast carcinoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…Correction for water T 1 and T 2 effects was implemented by allowing BayCEST to fit water T 1 and T 2 from the data, with prior values set based on the average T 1 and T 2 time within the whole rat brain or whole tumour for mice, yielding an APTR* value that is sensitive only to amide proton concentration and exchange rate (which is itself proportional to 10 pH ). A previous study (30) has shown that APTR* quantified using this analysis approach is specific to changes in protein concentration and pH in biologically relevant phantoms. The exchange rate and concentration estimated by BayCEST were used to generate an idealised two-pool Z-spectrum, and APTR* calculated using equation 1.…”
Section: Methodsmentioning
confidence: 93%
See 1 more Smart Citation
“…Correction for water T 1 and T 2 effects was implemented by allowing BayCEST to fit water T 1 and T 2 from the data, with prior values set based on the average T 1 and T 2 time within the whole rat brain or whole tumour for mice, yielding an APTR* value that is sensitive only to amide proton concentration and exchange rate (which is itself proportional to 10 pH ). A previous study (30) has shown that APTR* quantified using this analysis approach is specific to changes in protein concentration and pH in biologically relevant phantoms. The exchange rate and concentration estimated by BayCEST were used to generate an idealised two-pool Z-spectrum, and APTR* calculated using equation 1.…”
Section: Methodsmentioning
confidence: 93%
“…The APT effect from the measured CEST MRI data was quantified using the APTR* metric as described previously (25,2830). Briefly, data were fit to the Bloch-McConell equations using BayCEST in the FMRIB Software Library (FSL; https://fsl.fmrib.ox.ac.uk/fsl/fslwiki/baycest) assuming a 3-pool exchange model comprising water, amide protons at 3.5 ppm, and a combined NOE+MT pool at -2.41 ppm.…”
Section: Methodsmentioning
confidence: 99%
“…In study conducted by Sun et al APTW signal was significantly decrease in the ischemic region as the T1 was significantly increased compared with the contralateral normal area. In fact, more precise methods, including model-based approach ( 37 ), inverse metric approach ( 34 ) and T 1 / T 2 time compensated CESTR ( 38 ) have been used, which makes APT imaging more sensitive. Second, the sample size was relatively small and further investigations that involve a larger sample size are required.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have either quantified the MT effect using a qMT model, and then applied the qMT parameter estimates into a CEST analysis, or simply included the MT effect as an additional pool in a multi‐pool Lorentzian‐lineshape analysis, preventing comparison of these results with existing qMT literature. To the authors’ knowledge, only one quantitative analysis method, derived from the Bloch‐McConnell equations, has been developed that quantitatively estimates both the MT and CEST parameters simultaneously . Unfortunately, this methodology has not yet been used to explicitly measure the MT effect, instead modeling it as a combined term with nuclear Overhauser effect‐relayed exchange (NOE) .…”
Section: Introductionmentioning
confidence: 99%